ELECTROCHEMICAL STUDIES OF THE INHIBITING EFFICIENCY OF ANTICORROSION COATINGS - Kodirov N.U; Beknazarov Kh.S; Ibragimov B.T. (PT ANTIS International Publisher, 2024)
In this article, the polarization curves of anti-corrosion coatings are studied. Corrosion analysis of bare and coated substrates was performed using a CS-350 potentiostat system connected to corrosion analysis software. Polarization measurements were carried out potentiostatically at room temperature using an Ag/AgCl/Cl- (0.222 V) reference electrode and a platinum electrode. Potentiodynamic measurements were performed in the range from -2000 to 2000 mV vs. Ag/AgCl/Cl at a rate of 5 mV/s. Before the measurements, the electrodes were kept in the working solutions for at least 30 minutes to reach the steady state potential.